Research of the Fractal Extrapolation of Transmission System Load Signal of Tracked Vehicle - Wang Yanzhong; Chen Yanyan; Zhou Guangming; Jia Shuang; Lv Qingjun; Zhang Zuzhi (Jixie chuandong)
Aiming at the problem of load test data volume of transmission system of heavy tracked vehicles（HTVs） is huge and extraction rate of effective information is low,the inherent fractal hierarchical rule of this data is studied,this data have the typical fractal characteristic is verified and the fractal parameter of the tracked vehicle transmission system load data under a certain road condition.Under the premise of ensurse data accuracy and fractal character,a new fractal interpolation method（FIM） is built,the continuation to simplify data information is realized.Moreover,obvious advantages could be observed in the results of the FIM,comparing to those of the linear interpolation method and the spline interpolation method.It could be concluded that by combining a’low-frequency-and-long- time’ sampling approach and the proposed FIM,the test efficiency of load history can be improved,the complex chaotic feature of high frequency sampling data can be represented.And a analysis way for researching the dynamic chaos characteristic of the HTVs transmission system is provided.